The potential for using stable isotopes for solving urban geohydrological problems in the Cape Town area - Oom, Bruce Michael (Department of Geological Sciences, 2016)
This thesis investigates the potential for using the stable isotopes of hydrogen and oxygen from surface water and shallow aquifer water in solving urban geohydrological problems in the Cape Town metropolitan region. Three different water groups were chosen for detailed analysis, namely groundwater, springwater and reservoir water destined to join the mains water supply system. The stable isotope composition of groundwater and springwater were assumed to be fairly constant throughout the year, and were thus sampled only once. The reservoir waters were subject to evaporation effects, which result in isotope fractionation. The reservoir waters were sampled at the end of summer (9th April 1996), and near the end of winter (14th August 1996), in order to identify any seasonal isotope variations in the reservoir water isotope values. Reservoir water was sampled before and after the mains water treatment process, to identify any effect water treatment had on the isotope composition of the water. The two effects of water treatment and seasonal variation were determined simultaneously. Chemical analyses (pH, electrical conductivity, alkalinity, major anions and cations) of many of the water samples were performed to investigate the potential for correlating isotope values with chemical concentrations, and for using chemical analyses to complement or supplement isotope studies.